Role of β(1)-Integrin in Colorectal Cancer: Case-Control Study - Oh, Bo-Young (The Korean Society of Coloproctology, 2014)
PURPOSE: In the metastatic process, interactions between circulating tumor cells (CTCs) and the extracellular matrix or surrounding cells are required. β(1)-Integrin may mediate these interactions. The aim of this study was to investigate whether β(1)-integrin is associated with the detection of CTCs in colorectal cancer. METHODS: We enrolled 30 patients with colorectal cancer (experimental group) and 30 patients with benign diseases (control group). Blood samples were obtained from each group, carcinoembryonic antigen (CEA) mRNA for CTCs marker and β(1)-integrin mRNA levels were estimated by using reverse transcription-polymerase chain reaction, and the results were compared between the two groups. In the experimental group, preoperative results were compared with postoperative results for each marker. In addition, we analyzed the correlation between the expressions of β(1)-integrin and CEA. RESULTS: CEA mRNA was detected more frequently in colorectal cancer patients than in control patients (P = 0.008). CEA mRNA was significantly reduced after surgery in the colorectal cancer patients (P = 0.032). β(1)-Integrin mRNA was detected more in colorectal cancer patients than in the patients with benign diseases (P < 0.001). In colorectal cancer patients, expression of β(1)-integrin mRNA was detected more for advanced-stage cancer than for early-stage cancer (P = 0.033) and was significantly decreased after surgery (P < 0.001). In addition, expression of β(1)-integrin mRNA was significantly associated with that of CEA mRNA in colorectal cancer patients (P = 0.001). CONCLUSION: In conclusion, β(1)-integrin is a potential factor for forming a prognosis following surgical resection in colorectal cancer patients. β(1)-Integrin may be a candidate for use as a marker for early detection of micrometastatic tumor cells and for monitoring the therapeutic response in colorectal cancer patients.